The Constabulary of the Plains - Robert J. Smith; William McKale (Symphony in the Flint Hills, 2013)
The establishment and evolution of Fort Riley from the 1850s through the 21st century.
Keywords: Constabulary; Plains; Fort Riley; Ft. Riley; beauty; Kansas; Mexican-American War; nature; native; natural; Great Compromise 1850; Free-State; slavery; anti-slavery; pro-slavery; Bleeding Kansas; Calvary Parade Field; Kansas River; Wakarusa War; Shawnee Manual Labor School; territory; land; west; development; Quantrill; Civil War; Confederacy; Union; J.E.B Smart; Albert Sidney Johnston; Henry Heth; Lewis Armistead; John Sedgewick; Winfield Scott Hancock; Nathaniel Lyon; service; army; war; military; Battle of Wilson& #x27; s Creek; militia; guerilla; 7th Calvary Regiment; George A. Custer; Custer; Territorial Capital; Big Red One; 1st Infantry Division